Teacher Comments on The Contributions of Primary Education Curriculums to The Reflective Thinking Abilities of Students - Demiralp, Demet; Kazu, Hilal (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2012)
Development of higher order thinking skills of students is of great importance to the the 2005 primary education curriculums set forth on the basis of constructivist approach. One of the higher order thinking styles is reflective thinking. This study is performed to investigate the contributions of primary education curriculums to the development of reflective thinking abilities of students from the perspective of teacher comments. The study is descriptive and utilized survey method. 644 classroom teachers, who currently serve in the Elazig province particiated in the study. Data collected with a scale developed by the researchers and analyzed with statistical techniques such as frequencies, percentages, and means. Analysis of the data revealed that most of the teachers agreed with the thoughts that primary school curriculums contribute to the development of reflective thinking abilities of students. This finding shows that teacher perceptions on primary school curriculums from the angle of developing reflective thinking abilities of students are generally positive. According to the degree of teachers' agreements with the statements in the inventory, it can be concluded that the teachers think that the primary school curriculums, learning environment in general and evaluation processes effect the reflective thinking abilities of the student in a positive way. Together with this, according to the teacher perceptions, curriculums help students on their personal developments as a result of development on their reflective thinking abilities.
Keywords: Primary school curriculums; constructivist learning approach; reflective thinking